1995
DOI: 10.1016/0735-1097(94)00439-w
|View full text |Cite
|
Sign up to set email alerts
|

Relation of severity of symptoms to transient myocardial ischemia and prognosis in unstable angina

Abstract: Transient myocardial ischemia detected by Holter monitoring, but not chest pain, is the best predictor of unfavorable short-term clinical outcome. The decision to perform early angiography and revascularization cannot be based on symptoms alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…ST-segment monitoring stud-ies of patients hospitalized with unstable angina show that although 80% to 90% of transient ischemic events are asymptomatic, they are nonetheless significant markers for unfavorable short-and long-term outcomes (Table 2). [63][64][65][66][67][68][69][70] Patients Who Present to the ED With Chest Pain or Anginal Equivalent Symptoms It is not uncommon for patients with acute ST-elevation MI to have an initial ECG that is nondiagnostic for acute ischemia. Investigators who use continuous monitoring have shown that the ST segment often is dynamic in the early hours of acute MI.…”
Section: Patients In the Early Phase Of Acute Coronary Syndromes (St-mentioning
confidence: 99%
“…ST-segment monitoring stud-ies of patients hospitalized with unstable angina show that although 80% to 90% of transient ischemic events are asymptomatic, they are nonetheless significant markers for unfavorable short-and long-term outcomes (Table 2). [63][64][65][66][67][68][69][70] Patients Who Present to the ED With Chest Pain or Anginal Equivalent Symptoms It is not uncommon for patients with acute ST-elevation MI to have an initial ECG that is nondiagnostic for acute ischemia. Investigators who use continuous monitoring have shown that the ST segment often is dynamic in the early hours of acute MI.…”
Section: Patients In the Early Phase Of Acute Coronary Syndromes (St-mentioning
confidence: 99%
“…Indeed, continuous ST monitoring analyzes changing patterns of ST recovery and reelevation, which are associated with cyclic flow changes, 18,19 thus allowing a precise estimation of the total ischemic burden of patients with acute coronary syndromes. 22 There is now considerable evidence from multiple Holter studies in several thousand patients that ischemia-related signals detected by ECG monitoring are linked with major cardiovascular events during follow-up, 11,12,22 even in clinically stable patients. 23,24 …”
Section: The Role Of St Monitoringmentioning
confidence: 99%
“…17 Such an approach, however, is questionable, as some low-risk patients with a cardiac origin of their chest pain have a dynamic activity of the ST segment, 18,19 with most episodes of myocardial ischemia occurring in the absence of symptoms. 11,12 Therefore, standard 60 electrocardiography may miss ST changes when they are not associated with symptoms suggesting a cardiac origin. As a consequence, the optimal sampling interval for ECG tracings is unclear, as is the diagnostic and prognostic contribution of using single-lead or two-or three-lead ECG monitoring.…”
Section: Commonly Used Diagnostic Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12] Importantly, many studies have found that patients with ECG-detected ischemia, as compared to patients without such events, were at higher risk for unfavorable outcomes in both the short term [11][12][13] and long term. [14][15][16] Hence, symptoms are an unreliable indicator of ischemia in NSTEMI/UA, which is problematic since treatment decisions for an early invasive strategy or initial medication strategy are often driven by patient symptoms. [2][3][4][5] Further, biomarkers identify NSTEMI/UA patients too late because their presence in the serum indicates that cellular death has already occurred.…”
mentioning
confidence: 99%